2008
DOI: 10.4049/jimmunol.180.9.6385
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Non-Synonymous Polymorphism (p.Arg240His) in C4b-Binding Protein Is Associated with Atypical Hemolytic Uremic Syndrome and Leads to Impaired Alternative Pathway Cofactor Activity

Abstract: Atypical hemolytic uremic syndrome (aHUS) is a disorder characterized by hemolytic anemia, thrombocytopenia, and acute renal failure. Mutations, polymorphisms, and copy number variation in complement factors and inhibitors are associated with aHUS. In this study, we report the first functional non-synonymous polymorphism in the complement inhibitor C4b-binding protein (C4BP) α-chain (c.719G>A; p.Arg240His), which is associated with aHUS. This heterozygous change was found in 6/166 aHUS patients compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 42 publications
(46 reference statements)
2
43
0
Order By: Relevance
“…In addition, age at onset and severity of the disease may vary among family members with the same mutation ( Figure 5). The role of various polymorphisms as independent or additional susceptibility factors to aHUS has been demonstrated in the genes encoding CFH [18,26,[85][86][87], MCP [26,86], CFHR1 [88] or C4b-BP [89]. These sequence variations in the human genome are mostly changes of a single base (Single Nucleotide Polymorphism, SNP), which can be associated with a change of amino-acid in the protein, inducing a partial gain or loss of function.…”
Section: Familial Ahus Incomplete Penetrance and Genetic Variabilitymentioning
confidence: 99%
“…In addition, age at onset and severity of the disease may vary among family members with the same mutation ( Figure 5). The role of various polymorphisms as independent or additional susceptibility factors to aHUS has been demonstrated in the genes encoding CFH [18,26,[85][86][87], MCP [26,86], CFHR1 [88] or C4b-BP [89]. These sequence variations in the human genome are mostly changes of a single base (Single Nucleotide Polymorphism, SNP), which can be associated with a change of amino-acid in the protein, inducing a partial gain or loss of function.…”
Section: Familial Ahus Incomplete Penetrance and Genetic Variabilitymentioning
confidence: 99%
“…In the first, C3b was deposited on the sheep erythrocytes by sequential incubation of C1, C4, C2 and C3 [15]. To cleave the C3b, the erythrocytes were incubated with 5 mg/mL FI and 100 mg/mL C4BP at 371C for 60 min.…”
Section: Fi Degradation Of Surface-bound C3bmentioning
confidence: 99%
“…The familial form of aHUS has now been shown to be associated with genetic abnormalities in complement regulators like factor H (FH) [3][4][5][6], factor I (FI) [4,[7][8][9][10], membrane cofactor protein (MCP) Ã These authors contributed equally to this work. 172 [4,[11][12][13][14], C4b-binding protein (C4BP) [15], factor B (FB) [16] and C3 [17] or autoantibodies against FH [18,19]. The mutations and polymorphisms in these proteins are mostly found in heterozygous form and can affect both the secretion and function of the proteins, leading to impaired regulation of the alternative pathway of the complement system [2].…”
mentioning
confidence: 99%
“…At present, only one functional non-synonymous polymorphism (R240H) has been identified that does not affect expression, but C3b binding and its cofactor functions both in fluid phase and on the cell surface are diminished. 17 This polymorphism has been associated with aHUS, a disease in which excessive complement activation was shown to play a pathogenic role. The anti-C5 mAb eculizumab is currently the only accepted treatment.…”
mentioning
confidence: 99%